Fundamental Methodology of Prognosis of Temperature Stresses and Deformations in Frozen Soils (K Osnovam Metodiki Prognoza Temperaturnykh Napriazhenii i Deformatsii v Merzlykh Gruntakh) - Grechishehev,S. E. (1975)
The amount of moisture in the frozen ground exerts a very great effect on the temperature stress dynamics. Calculations are made by the author which show that in most cases at depth equalling about 2/3 of the active layer, during the first half of the cold season, the stresses should be the tensile type. At the same type the upperlayers could also be compressive, within the limits of the active layer, it can develop that at an identical time, in the upper horizons we will record compression while in the lower horizons, we will find tension. This is indicative of the important conclusion to the effect that part of the frost clefts could form at a certain depth and not emerge to the surface. Draft trans. of Vsesoyuznyi Nauchno-Issledovatelskii Institut Gidro-Geologii i Inzhenernoi Geologii. Trudy (USSR) p1-53 1970.